PENGGUNAAN JENIS DAN DOSIS PUPUK ANORGANIK DENGAN PENGAYAAN FESES SAPI PERAH PADA DIAMETER BATANG DAN PRODUKSI BAHAN KERING RUMPUT GAJAH (Pennisetum purpureum Schumach) - Denni Irawan; Nur Hidayat; Eko Hendarto (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The study entitled Use of Types and Dosages of Inorganic Fertilizers with Enrichment of Dairy Cattle Stool on Stem Diameter and Dry Matter Production of Elephant Grass (Pennisetum purpureum Schumach). This study aims to determine the best combination of types and levels of inorganic fertilizers into dairy cow feces on elephant grass growth (Pennisetum purpureum Schumach). Materials and Methods. The research materials included 162 cuttings of elephant grass (Pennisetum purpureum Schumach), dairy cow feces 3 kg/m2, urea, NPK, and ZA fertilizers. The research method is experimental with the basic design factorial pattern Completely Randomized Design (CRD). The first factor is the type of fertilizer and the second factor is the dose of inorganic fertilizer 100-300 kg/ha/def equivalent to the nitrogen content of urea. Results. The results of the analysis of variance showed that the use of fertilizer doses had a very significant effect (F count > F table 0.01) on stem diameter, the type of fertilizer had a significant effect (F count > F table 0.05) on dry matter production. A further test of honest significant difference (BNJ) was carried out on the type of fertilizer and a regression test on the dose of fertilizer. Conclusion. the administration of ZA at a dose of 300 kg/ha/def and NPK at a dose of 300 kg/ha/def gave the highest stem diameter and dry matter production of elephant grass (Pennisetum purpureum Schumach) with an average value of 16.53 mm and 1.649 kg/m2.